2017
DOI: 10.1002/lno.10636
|View full text |Cite
|
Sign up to set email alerts
|

The role of subduction and gravitational sinking in particle export, carbon sequestration, and the remineralization length scale in the California Current Ecosystem

Abstract: Particles and aggregates created in the surface layers of the ocean are transported not only by gravity, but also by the horizontal and vertical advection of the surrounding water. Subduction, in particular, can transport organic matter from the surface ocean to the mesopelagic in a manner that is not likely to be detected by typical in situ carbon export measurements (e.g., sediment traps and 238 U-234 Th disequilibrium). To assess the importance of subduction to the biological pump, we combined in situ sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 105 publications
(129 reference statements)
6
64
0
Order By: Relevance
“…However, because these events are relatively rare and limited in space and time, their contribution to the annual and regional carbon export is still about 10 times smaller than the gravitational pump (Figure ). This result is consistent with the study of Stukel, Song, et al (), which showed that, in the California Current, sinking particles were more efficiently exported at depth than subducted particles.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…However, because these events are relatively rare and limited in space and time, their contribution to the annual and regional carbon export is still about 10 times smaller than the gravitational pump (Figure ). This result is consistent with the study of Stukel, Song, et al (), which showed that, in the California Current, sinking particles were more efficiently exported at depth than subducted particles.…”
Section: Resultssupporting
confidence: 93%
“…The compensation between upward and downward transport is, however, not complete. In line with previous observations and modeling studies (Llort et al, ; Omand et al, ; Stukel, Aluwihare, et al; Stukel, Song, et al), we find that the downward transport of POC across the euphotic layer (8 mg C·m −2 ·day −1 ) exceeds the upward transport of POC (7 mg C·m −2 ·day −1 ) because of the asymmetric effect of upward and downward velocities on the vertical gradient in particles (sharp decline with depth, Figure ). The integrated effect of eddy‐driven POC subduction is, however, small and accounts for less than 2% of the annual POC export at the regional scale.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations